2006
DOI: 10.1007/s00421-006-0236-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of aerobic and anaerobic energy production during exhaustive exercise on a cycle ergometer

Abstract: An extension of the original hyperbolic model (Model-2) was proposed by using power output required to elicit maximal oxygen uptake (Pt). This study aimed to test this new model (Model-alpha) using mechanical work produced during cycle ergometry. Model alpha assumed that power exceeding a critical power (Pc) was met partly by the anaerobic metabolism. The parameter alpha was the proportion of the power exceeding Pc provided by anaerobic metabolism, while power exceeding Pt was exclusively met by anaerobic meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Previous applications of the segmented model postulated that the rise in _ VO 2 could be described by a mono-exponential function Chatagnon and Busso 2006). The analysis of the sensitivity to the value chosen for the time constant showed that it affected only the estimates of W 0 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous applications of the segmented model postulated that the rise in _ VO 2 could be described by a mono-exponential function Chatagnon and Busso 2006). The analysis of the sensitivity to the value chosen for the time constant showed that it affected only the estimates of W 0 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Schematic representation of how the segmented model describes the aerobic (P aer ) and anaerobic (P anaer ) contribution to total power output according to P c and P t , the critical power and the power eliciting maximal aerobic power, respectively. The curves were built with the average data from Chatagnon and Busso (2006), i.e. P c = 201 W, P t = 295 W and a = 0.446 giving P aermax = 253 W A target pedalling frequency of 75 rpm was imposed using a metronome.…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the simplifying assumption is also made that the anaerobic contribution to the overall energy requirement is nil up to _ VO 2max ; a fact that is not always necessarily true (e.g. see Busso and Chatagnon 2006;Chatagnon and Busso 2006).…”
Section: Discussionmentioning
confidence: 99%
“…During this work/ ventilation mismatch, an individual's energy needs are met by anaerobic processes (McArdle et al, 2001). Complete utilization of the anaerobic work capacity has been used to model the point at which an individual is exhausted (Chatagnon and Busso, 2006). A measure of this anaerobic work is the magnitude of mismatch between energy expenditure and oxygen consumption.…”
Section: Methodsmentioning
confidence: 99%